2009
DOI: 10.1186/1746-6148-5-43
|View full text |Cite
|
Sign up to set email alerts
|

Survival potential of wild type cellulose deficient Salmonella from the feed industry

Abstract: BackgroundBiofilm has been shown to be one way for Salmonella to persist in the feed factory environment. Matrix components, such as fimbriae and cellulose, have been suggested to play an important role in the survival of Salmonella in the environment. Multicellular behaviour by Salmonella is often categorized according to colony morphology into rdar (red, dry and rough) expressing curli fimbriae and cellulose, bdar (brown, dry and rough) expressing curli fimbriae and pdar (pink, dry and rough) expressing cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 38 publications
(60 reference statements)
4
54
1
Order By: Relevance
“…Most S. enterica wild-type strains display curli fimbriae in the matrix, but the percentage of strains with cellulose varies from 40 to 100, depending on the serovar and the source of isolation (31,32). Variations between E. coli strains have also been observed (unpublished results).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Most S. enterica wild-type strains display curli fimbriae in the matrix, but the percentage of strains with cellulose varies from 40 to 100, depending on the serovar and the source of isolation (31,32). Variations between E. coli strains have also been observed (unpublished results).…”
mentioning
confidence: 84%
“…In all, six S. enterica and four E. coli wildtype strains, as well as two S. enterica ⌬rpoS mutants, were included ( Table 1). The strains displayed variations in the composition of the biofilm matrix, visualized as different morphotypes on Congo red or Coomassie brilliant blue agar, as described previously (31). The morphotypes were categorized as follows: (i) rdar (red, dry, and rough), indicating matrix with curli fimbriae and cellulose; (ii) bdar (brown, dry, and rough), indicating biofilm matrix with curli fimbriae and without cellulose; and (iii) saw (smooth and white), indicating no biofilm formation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prouty & Gunn (2003) identified its crucial importance for biofilm formation on glass coverslips. However, cellulose was not a major constituent of the biofilm matrix of S. Agona and S. Typhimurium strains isolated from the feed industry, but it contributed to the highly organized matrix structurization (Vestby et al, 2009a). Malcova et al (2008) found that cellulose was not crucial for S. Enteritidis adherence and biofilm formation on polystyrene.…”
Section: Molecular Components Of Salmonella Biofilms Formed On Abiotimentioning
confidence: 99%
“…Another important structure was recently found in Salmonella Enteritidis strains -the surface protein Bap A (biofilmassociated protein) (Latasa et al, 2005). Besides the celulose, an important polysaccharide component is also the colanic acid, and in some serotypes of Salmonella unknown polysaccharides have been found (Vestby et al, 2009). …”
Section: Introductionmentioning
confidence: 99%